Efeito do hipotireoidismo gestacional experimental associado à dieta hiperlipídica no metabolismo e no comportamento ingestivo da prole de ratas - Carvalho, Vanessa Cibelle Barboza de (2014)
Gestational hypothyroidism is considerably prevalent. Low maternal thyroid hormones (THs) levels during pregnancy may affect several physiological systems in the offspring. Similarly, an inadequate maternal nutrition during pregnancy is implicated as the origin of many metabolic and cardiovascular diseases in the offspring. Therefore, gestational hypothyroidism, in addition to an inadequate maternal nutrition could trigger an even worse profile in the neuroendocrine, metabolic and feeding behavior throughout postnatal life of the offspring. The aim of this study was to assess metabolic aspects and ingestive behavior of the offspring of rats treated with high fat diet (HD) during gestation associated with experimental gestational hypothyroidism (EGH). On gestational day (GD) 3, we started to feed pregnant rats with the HD, and on GD 9, we started to induce EGH with 0.02% methimazole in drinking water, ad libitum. HD and EGH were only interrupted on the day of birth. The pregnant rats were weighted and monitored for the amount of food and water ingested from GD 3 up to GD 20. In the offspring, body development indexes were measured from postnatal day (PND) 1 up to PND 120. At PND 60, we performed the insulin tolerance test (ITT), glucose tolerance test (GTT), biochemical measurements, in both genders. Furthermore, food, water and 0.3 M NaCl ingestive behaviors were measured in male offspring at PND 30, 60, 90 and 120. Data were analyzed by two- or three-way ANOVAs with Bonferroni posttest. Male offspring from hypothyroid rats submitted to HD (OHT + HD) showed higher hematocrit, triglycerides, cholesterol and urea sera levels when compared to male offspring from hypothyroid rats submitted to control diet (OHT + CD). Moreover, female OHT + HD had higher glucose sensitivity at 30 minutes on the GTT when compared to OHT + CD (p<0.05) and also to offspring from euthyroid rats (OET) + HD (p<0.01). However, we observed no differences in fasting glycemia and ITT in female offspring from different groups. In conclusion, the association of EGH and HD during gestation caused a significant deficit in body development and dyslipidemia in male offspring, whereas female offspring exhibit higher glucose sensitivity. Thus, this data show, for the first time, how the association between low maternal THs with HD predict an abnormal metabolic profile in offspring, and give us an insert about the origin of several unknown metabolic diseases.